2018
DOI: 10.7759/cureus.2472
|View full text |Cite
|
Sign up to set email alerts
|

Infection-associated Hemophagocytic Lymphohistiocytosis: An Unusual Clinical Masquerader

Abstract: Hemophagocytic lymphohistiocytosis (HLH) secondary to an infection is a great impersonator. It is caused by hyperimmune activation, which leads to a wide array of hematological abnormalities. If the disease is untreated, it is usually fatal. We report the case of a four-year-old girl who presented to our tertiary care hospital with high-grade fever, frequent loose stools, and bleeding from the lips and gums. Investigations showed pancytopenia, hyperferritinemia, hypofibrinogenemia, and hypertriglyceridemia whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Caksen et al reported a sHLH patient associated with typhoid fever was given oral chloramphenicol for 14 days, who was symptom-free during a 7-month of follow-up [14]. Awais Abbas et al reported a sHLH patient triggered by Salmonella enterica serotype typhi (S. enterica serotype typhi) was started on ceftriaxone, later switched the regimen to tazobactam and vancomycin, and discharged after 32 days [15]. Lemuel et al reported a patient with S. enterica serovar typhi related sHLH who started empirically on intravenous vancomycin, cefepime, and doxycycline, and eventually de-escalated to intravenous ceftriaxone, who discharged 2 weeks later [16].…”
Section: Discussionmentioning
confidence: 99%
“…Caksen et al reported a sHLH patient associated with typhoid fever was given oral chloramphenicol for 14 days, who was symptom-free during a 7-month of follow-up [14]. Awais Abbas et al reported a sHLH patient triggered by Salmonella enterica serotype typhi (S. enterica serotype typhi) was started on ceftriaxone, later switched the regimen to tazobactam and vancomycin, and discharged after 32 days [15]. Lemuel et al reported a patient with S. enterica serovar typhi related sHLH who started empirically on intravenous vancomycin, cefepime, and doxycycline, and eventually de-escalated to intravenous ceftriaxone, who discharged 2 weeks later [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, HLH secondary to typhoidal Salmonella infection has been reported in a few cases. One case report described a previously healthy four-year-old girl with HLH secondary to Salmonella typhi [ 9 ] and another case report discussed a rare presentation of typhoid fever with meningitis and secondary HLH in a previously healthy five-year-old child [ 10 ]. Both patients in the above-mentioned case reports had no evidence of immune deficiencies [ 9 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case report described a previously healthy four-year-old girl with HLH secondary to Salmonella typhi [ 9 ] and another case report discussed a rare presentation of typhoid fever with meningitis and secondary HLH in a previously healthy five-year-old child [ 10 ]. Both patients in the above-mentioned case reports had no evidence of immune deficiencies [ 9 - 10 ]. The severe presentation in our patient seems to be due to the underlying IL12Rβ1 deficiency, which selectively predisposes the affected individual to infections with non-typhoidal Salmonella among other intracellular pathogens [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhoea and bowel symptoms are not part of the formal HLH 2004 or HLH 2008 diagnostic criteria, and as a result, the presence of diarrhoea in HLH/MAS is not well-described in the literature 11. A handful of case reports have noted an association between HLH and diarrhoea secondary to various abdominal pathologies such as appendicitis, IBD, infectious colitis and T-cell lymphoma 38–42. Pagel et al identified a subtype of inherited familial HLH (type 5 familial HLH) presenting with copious, severe, chronic watery diarrhoea, in which defects in the lysosomal-dependent exocytosis pathway (STXBP2) were inherited in an autosomal recessive manner 43.…”
Section: Discussionmentioning
confidence: 99%